2017
DOI: 10.1186/s12864-017-3547-3
|View full text |Cite
|
Sign up to set email alerts
|

An integrative metabolomics and transcriptomics study to identify metabolic alterations in aged skin of humans in vivo

Abstract: BackgroundAging human skin undergoes significant morphological and functional changes such as wrinkle formation, reduced wound healing capacity, and altered epidermal barrier function. Besides known age-related alterations like DNA-methylation changes, metabolic adaptations have been recently linked to impaired skin function in elder humans. Understanding of these metabolic adaptations in aged skin is of special interest to devise topical treatments that potentially reverse or alleviate age-dependent skin dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 90 publications
2
67
1
Order By: Relevance
“…Among the most reduced proteins with age in the buttock were phosphoglycerate mutase 1, proteasome alpha subunits and inositol monophosphatase 2. A recent transcriptome study found inositol monophosphatase 2 to be higher in aged skin [53], however in this study we found the opposite to be true at the protein level. It is possible that the increase in the transcription of this enzyme is in response to lower cellular levels of the protein, if with age the rate of turnover increases or the rate of translation reduces.…”
Section: Protein Abundance In Young and Aged Photoexposed Forearm Skincontrasting
confidence: 97%
“…Among the most reduced proteins with age in the buttock were phosphoglycerate mutase 1, proteasome alpha subunits and inositol monophosphatase 2. A recent transcriptome study found inositol monophosphatase 2 to be higher in aged skin [53], however in this study we found the opposite to be true at the protein level. It is possible that the increase in the transcription of this enzyme is in response to lower cellular levels of the protein, if with age the rate of turnover increases or the rate of translation reduces.…”
Section: Protein Abundance In Young and Aged Photoexposed Forearm Skincontrasting
confidence: 97%
“…Since the microbiome and metabolite profiles are influenced by the environment, nutrition, age, and lifestyle of the host, in addition to genetics, these concatenated profiles provide a unique snapshot of individual health. 19,22,31,[23][24][25][26][27][28][29][30] Indeed, while these complex profiles can be examined independently, changes in the collective abundance patterns of metabolites and microbes may indicate deeper homeostatic disturbances, which may be reflected through changes in interleukin signaling. The membership of the bodies microbial communities have dynamic interconnected relationships with one another and the host that change under states of disease and stress.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolome and microbiome 21 are also unique portraits of the individual patient as they are not only influenced by genetics and disease state but also by the environment, nutrition, age, and lifestyle 19,22,31,[23][24][25][26][27][28][29][30] . Thus the microbiome and metabolome are very different from transcriptomic or proteomic biomarkers.…”
Section: Introductionmentioning
confidence: 99%
“…Integrative metabolomics and transcriptomics were later applied to show global metabolic adaptations occurring in epidermal skin during aging. [ 115 ] Microarray analysis of the transcriptome was performed on epidermal tissue samples from 24 young and 24 old donors, of which 23 donors of each group were also included in the metabolomics analysis. The results of the study revealed age‐dependent reduction of coenzyme Q10 levels, as well as altered activity in upper glycolysis and glycerolipid biosynthesis or decreased protein and polyamine biosynthesis.…”
Section: Omics‐based Molecule‐pattern Biomarkersmentioning
confidence: 99%
“…The results of the study revealed age‐dependent reduction of coenzyme Q10 levels, as well as altered activity in upper glycolysis and glycerolipid biosynthesis or decreased protein and polyamine biosynthesis. [ 115 ] Importantly, the identified compendium of age‐dependent genes (1053 transcripts with decreased and 932 transcripts with increased levels) had no significant overlap with reported genes predicted to be involved in aging in humans in other tissues. This indicates that each tissue of our body has its own age‐dependent gene expression pattern.…”
Section: Omics‐based Molecule‐pattern Biomarkersmentioning
confidence: 99%